New horizons of genomic in situ hybridization - Markova, M; Vyskot, B (Cytogenetic and genome research, 2009)
This review summarizes conventional and recent applications of genomic in situ hybridization (GISH). GISH is a well recognized technique, but its modifications and applications have not been widely used. Here, we show how modifications to the GISH technique can be used as tools to 'paint' plant chromosomes. In addition, we describe novel applications, e.g. how GISH banding could be used for karyotyping plant chromosomes. We further discuss recent phylogenetic applications of GISH that allow a semiquantitative signal analysis and the possibility of comparing and combining this cytogenetic technique with DNA sequence-based phylogenetic trees.
Keywords: Chromosomes, Plant; karyotypizace; Animals; Humans; chromozomy rostlin; sekvence nukleotidů; Base Sequence; lidé; Karyotyping; Phylogeny; zvířata; fylogeneze; In Situ Hybridization; hybridizace in situ